Chronotypes in Patients with Epilepsy: Does the Type of Epilepsy Make a Difference? - Hallie Kendis; Kelly Baron; Stephan U. Schuele; Bhavita Patel; Hrayr Attarian (Behavioural Neurology)
Circadian rhythms govern all biological functions. Circadian misalignment has a major impact on health. Late chronotype is a risk factor for circadian misalignment which in turn can affect the control of seizures in epilepsy patients. We compared a group of 87 confirmed epilepsy patients regardless of subtypes with age- and sex-matched healthy controls. We compared generalized epilepsy patients with localization related epilepsy patients and with healthy controls. We found that primary generalized epilepsy patients were 5 times more likely to have a late chronotype than healthy controls. We did not find any significant differences between localization related epilepsy patients and healthy controls or between the overall epilepsy cohort and healthy controls. Generalized epilepsy patients are more likely to be evening types as compared to those with focal epilepsy or subjects without epilepsy. Epilepsy patients do not experience the same age related increase in morningness as do age-matched healthy controls. This is important in regard to timing of AED, identifying and preventing sleep deprivation, and integrating chronotype evaluations and chronotherapy in comprehensive epilepsy care. Further studies, using objective phase markers or the impact of chronotherapy on seizure control, are necessary.